Answer:
n = 0
Step-by-step explanation:
1.2n + 1 = 1 - n
Add n and - 1 on both sides.
1.2n + n = 1 - 1
Combine like terms.
2.2n = 0
Divide both sides by 2.2.
n = 0
Answer:
0. 33 por que los jamones sivieron a 15 pesos y mi mama se va asta otro lado para compralo
One to one or injective means that each x in the domain maps to a unique y, i.e. the function preserves distinction.
y=(x-1)/(3x+3) is one to one. We can solve for x:
3xy + 3y = x - 1
3y + 1 = x - 3xy = x(1-3y)
x = (3y+1)/(1-3y)
That proves it's one-to-one; for each y we get one x.
![y=\sqrt{5x+9}](https://tex.z-dn.net/?f=y%3D%5Csqrt%7B5x%2B9%7D)
That's also one to one,
![y^2 = 5x+9](https://tex.z-dn.net/?f=y%5E2%20%3D%205x%2B9)
![x = \frac 1 5 (y^2 - 9)](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%201%205%20%28y%5E2%20-%209%29)
That's the proof.
![f(x)=\dfrac{7}{4x^2}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cdfrac%7B7%7D%7B4x%5E2%7D)
That's Not one-to-one
because f(-x)=f(x). We only need a single counterexample; f(1)=7/4, f(-1)=7/4
![f(x) = \frac 1 2 x^3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%201%202%20x%5E3)
That's one-to-one, textbook case
![f(x)=3x^4 + 7x^3](https://tex.z-dn.net/?f=f%28x%29%3D3x%5E4%20%2B%207x%5E3)
That's not one-to-one because the fourth power dominates so this will be sort of parabola-ish, repeating the same big positive values for a negative and positive x.
--------------
![y = f(x) = \sqrt[3]{x-2} + 8](https://tex.z-dn.net/?f=y%20%3D%20f%28x%29%20%3D%20%5Csqrt%5B3%5D%7Bx-2%7D%20%2B%208)
![y - 8 = \sqrt[3]{x-2}](https://tex.z-dn.net/?f=y%20-%208%20%3D%20%5Csqrt%5B3%5D%7Bx-2%7D)
![(y-8)^3 = x-2](https://tex.z-dn.net/?f=%28y-8%29%5E3%20%3D%20x-2)
![x = (y - 8)^3 + 2](https://tex.z-dn.net/?f=x%20%3D%20%28y%20-%208%29%5E3%20%2B%202)
![f^{-1}(x) =(x - 8)^3 + 2](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%28x%20-%208%29%5E3%20%2B%202)
First choice
Answer:
1.267650600228229401496703205376e+130
Step-by-step explanation:
√400 =20
20¹⁰⁰ = 1.267650600228229401496703205376e+130
Hope this helps!